48 Darbepoetin enhances endothelial-dependent vasomotor function in patients with stable coronary artery disease only after preceding ischaemia-reperfusion. (9th June 2011) - Tilling, L M; Hunt, J; Donald, A; Clapp, B; Chowienczyk, P
Abstract : Background: Vasoprotective effects of erythropoietin in animal models are mediated by endothelium-derived nitric oxide (NO) and/or mobilisation of endothelial progenitor cells (EPC) and may be enhanced by ischaemia; whether they are present in humans is unknown. We examined whether the erythropoietin analogue darbepoetin improves flow mediated dilatation (FMD), a measure of endothelium-derived NO, and whether this is influenced by preceding ischaemia-reperfusion. Methods: 36 patients (50–75 years) with stable coronary artery disease were randomised to receive a single dose of darbepoetin 300 μg or saline placebo. Immunoreactive erythropoietin was measured by an enzyme linked immunospecific assay. FMD was measured at the brachial artery using high resolution ultrasound. CD34+/VEGFR2+/133+ circulating EPC were enumerated by flow cytometry. Measurements were made immediately before darbepoetin/placebo and at 24 h, 72 h and 7 days. At 24 h FMD was repeated after 20 min ischaemia-reperfusion of the upper limb. A further group of 11 patients were studied according to the same protocol, all receiving darbepoetin, with omission of forearm ischaemia-reperfusion at 24 h. Results: Immunoreactive erythropoietin peaked at 24 h in the darbepoetin group (median value of 724 U/l (IQR 576–733 U/l), compared to 12 U/l (IQR 9–21 U/l) in the placebo group) and remained elevated at approximately 500 fold baseline at 72 h. FMD did not differ significantly between groups at 24 h (before ischaemia-reperfusion). At 72 h, (48 h after ischaemia-reperfusion) FMD increased from baseline in the darbepoetin group but not in the placebo group so that FMD (and change in FMD from baseline) was significantly greater in the darbepoetin group (change from baseline 1.7±0.3% and −0.6±0.4% in darbepoetin and placebo groups respectively, p<0.001).The increase in FMD at 72 h after darbepoetin and ischaemia-reperfusion at 24 h was significantly greater than that without preceding ischaemia-reperfusion (p<0.01). A ∼20% increase in CD133+/VEGFR2+ cells after darbepoetin was temporally dissociated with the increase in FMD. Conclusions: Preceding ischaemia-reperfusion is required for darbepoetin to enhance endothelial function, possibly by increasing expression of the erythropoietin receptor and by a mechanism likely to involve Akt/NO rather than circulating EPC.